Two new species of the genus Friesea (Collembola: Neanuridae) from North-west China - Gao, Yan; Yin, Wenying (Zootaxa, 2006)
Two undescribed species of the genus Friesea were found from Guangtou Mountain, Chang’an city, Shaanxi Province, north-west China. They are described as new species in this paper. F. shaanxiensis sp. nov. has six anal spines and no furca. F. quadrispinensis sp. nov. has four anal spines.